2018
DOI: 10.1080/12298093.2018.1468055
|View full text |Cite
|
Sign up to set email alerts
|

Biocontrol of Orchid-pathogenic Mold,Phytophthora palmivora, by Antifungal Proteins fromPseudomonas aeruginosaRS1

Abstract: Black rot disease in orchids is caused by the water mold Phytophthora palmivora. To gain better biocontrol performance, several factors affecting growth and antifungal substance production by Pseudomonas aeruginosa RS1 were verified. These factors include type and pH of media, temperature, and time for antifungal production. The results showed that the best conditions for P. aeruginosa RS1 to produce the active compounds was cultivating the bacteria in Luria-Bertani medium at pH 7.0 for 21 h at 37 °C. The cult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 46 publications
1
14
0
Order By: Relevance
“…The experiment was repeated three times with three replications per treatment. The growth inhibition of oomycete pathogens was calculated using the following formula: Inhibition (%) = [(α − β)/α] × 100, where α was the radial growth of phytopathogenic oomycete on the control plate and β was the radial growth of phytopathogenic oomycete on the dual culture plate [ 24 , 26 , 27 , 28 ].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The experiment was repeated three times with three replications per treatment. The growth inhibition of oomycete pathogens was calculated using the following formula: Inhibition (%) = [(α − β)/α] × 100, where α was the radial growth of phytopathogenic oomycete on the control plate and β was the radial growth of phytopathogenic oomycete on the dual culture plate [ 24 , 26 , 27 , 28 ].…”
Section: Methodsmentioning
confidence: 99%
“…Among the various methods, the use of plant growth-promoting rhizobacteria (PGPR) has attracted attention of many researchers. PGPR can control pathogenic oomycetes and increase plant growth [ 23 , 24 , 25 , 26 , 27 , 28 ]. Moreover, PGPR are well-known non-toxic bacteria that enhance soil fertility without causing negative effects on human health and the environment [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…BS1 inhibited the zoosporangium formation and zoospore germination of P. sojae , and the inhibition rate of stock solutions reaches 95.9% [13]. Sowanpreecha and Rerngsamran [14] found that the antibacterial protein from P. aeruginosa RS1 can effectively inhibit P. palmivora , and the molecular weight of the antibacterial protein is about 20 kDa to 54 kDa. According to LC/MS, these proteins may be catalase, chitin-binding protein, and protease.…”
Section: Introductionmentioning
confidence: 99%